3-4(9d+12)=-9(3d-12)

Simple and best practice solution for 3-4(9d+12)=-9(3d-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-4(9d+12)=-9(3d-12) equation:



3-4(9d+12)=-9(3d-12)
We move all terms to the left:
3-4(9d+12)-(-9(3d-12))=0
We multiply parentheses
-36d-(-9(3d-12))-48+3=0
We calculate terms in parentheses: -(-9(3d-12)), so:
-9(3d-12)
We multiply parentheses
-27d+108
Back to the equation:
-(-27d+108)
We add all the numbers together, and all the variables
-36d-(-27d+108)-45=0
We get rid of parentheses
-36d+27d-108-45=0
We add all the numbers together, and all the variables
-9d-153=0
We move all terms containing d to the left, all other terms to the right
-9d=153
d=153/-9
d=-17

See similar equations:

| 6z=33 | | y-8.9=7 | | 15-3x=5+7.5x | | 9x²-36x+36=0 | | 5(2x=1)-7(3x-4) | | -4f+11=29 | | 3k-5=3k-1 | | 15+0.50m=25m+0.25m | | 3(k-8)-5k=k-24 | | 17=n/2+12 | | -2x-1.4=6+3x | | -2|7-3y|-6=14 | | 14x-1+18x-2=35 | | -5x-26=4x+10 | | 5(m-1)=-24 | | 4x-4(7-5x=-20 | | 4q(q+1)2(4q+5)=0 | | z−49−13=59 | | -2.06f+18=-10.84 | | ⅓(t+6)-10=-3t+2 | | 4x+19=3+7x-8 | | 4x-60=-72 | | x=1.333*(x-90000) | | 4x+3=-4+2x+15 | | 9.6x-15.4=-4.3x+26.3 | | 4x-60=72 | | 4x+19=5x+7 | | -63=7g-14g= | | x/3=8/11 | | 2-3x3=3 | | 3m+6=6m | | 4|7y+2|-8=-7 |

Equations solver categories